The Relationship Between Carbohydrate Intake and Physical Activity with Body Mass Index in Medical Students - Suzan, Raihanah; Syofira, Novianti; Halim, Rita; Istarini, Attiya; Lipinwati, Lipinwati (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2025)
Background: The Body Mass Index (BMI) of medical students is influenced by dietary habits, lifestyle choices, and socio-cultural factors. The unique lifestyle and academic pressures faced by medical students make it essential to understand the relationship between carbohydrate intake, physical activity, and BMI in this population. Methods: This cross-sectional analytical study was conducted among 102 medical students at Jambi University, selected through purposive sampling. Data were collected using the International Physical Activity Questionnaire (IPAQ), a 2x24-hour food recall questionnaire, and anthropometric measurements of height and weight. Statistical analysis was performed using the Spearman correlation test. Results: The majority of respondents had low carbohydrate intake (85.3%), moderate physical activity levels (52.9%), and normal BMI (44.1%). Spearman correlation analysis showed no significant relationship between carbohydrate intake and BMI (p = 0.3, r = 0.1). However, a statistically significant negative correlation was found between physical activity and BMI (p < 0.001, r = -0.43), indicating that higher physical activity levels are associated with lower BMI. Conclusion: This study found no significant relationship between carbohydrate intake and BMI but identified a negative correlation between physical activity and BMI among medical students. These findings highlight the importance of promoting physical activity as the key factor in maintaining a healthy BMI.